2013
DOI: 10.3390/nu5082860
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Vitamin C Homeostasis during Deficiency

Abstract: Large cross-sectional population studies confirm that vitamin C deficiency is common in humans, affecting 5%–10% of adults in the industrialized world. Moreover, significant associations between poor vitamin C status and increased morbidity and mortality have consistently been observed. However, the absorption, distribution and elimination kinetics of vitamin C in vivo are highly complex, due to dose-dependent non-linearity, and the specific regulatory mechanisms are not fully understood. Particularly, little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
134
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(139 citation statements)
references
References 140 publications
(224 reference statements)
1
134
0
4
Order By: Relevance
“…Humans, non-human primates (including macaque monkeys), and guinea pigs cannot synthesize ascorbate from glucose, unlike other animals that have the enzyme required for the last step in ascorbate biosynthesis. The uptake and distribution of Vit C in the body is under homeostatic control and is regulated by tissue-specific sodium-dependent Vit C co-transporters (SVCT) 1 and 2, which actively transport Vit C (Tsukaguchi et al, 1999;Fischer et al, 2004;Corti et al, 2010;Lindblad et al, 2013). In the body, Vit C displays complex non-linear pharmacokinetics, and in brain tissue the Vit C is present at higher concentrations than in other organs (Kaufman, 1966;Spector, 1977;Schreiber and Trojan, 1991;Lindblad et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Humans, non-human primates (including macaque monkeys), and guinea pigs cannot synthesize ascorbate from glucose, unlike other animals that have the enzyme required for the last step in ascorbate biosynthesis. The uptake and distribution of Vit C in the body is under homeostatic control and is regulated by tissue-specific sodium-dependent Vit C co-transporters (SVCT) 1 and 2, which actively transport Vit C (Tsukaguchi et al, 1999;Fischer et al, 2004;Corti et al, 2010;Lindblad et al, 2013). In the body, Vit C displays complex non-linear pharmacokinetics, and in brain tissue the Vit C is present at higher concentrations than in other organs (Kaufman, 1966;Spector, 1977;Schreiber and Trojan, 1991;Lindblad et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…The uptake and distribution of Vit C in the body is under homeostatic control and is regulated by tissue-specific sodium-dependent Vit C co-transporters (SVCT) 1 and 2, which actively transport Vit C (Tsukaguchi et al, 1999;Fischer et al, 2004;Corti et al, 2010;Lindblad et al, 2013). In the body, Vit C displays complex non-linear pharmacokinetics, and in brain tissue the Vit C is present at higher concentrations than in other organs (Kaufman, 1966;Spector, 1977;Schreiber and Trojan, 1991;Lindblad et al, 2013). Additionally, the brain is able to preferentially retain Vit C at the expense of other tissues during chronic states of severe deficiency, and to uphold concentrations 100-fold higher than other organs, which are readily depleted (Hughes et al, 1971;Lykkesfeldt et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The SVCTs show distinct tissue distribution, and together ensure the effective uptake and regulation of plasma and cellular ascorbate concentrations [36,35]. SVCT1 is responsible for uptake through the gut and re-absorption in the kidneys, and is thought to largely regulate plasma levels, whereas SVCT2 is concentrated in more metabolically active cells throughout the body, ensuring an adequate intracellular supply to support crucial intracellular functions [36,35]. Both SVCT1 and SVCT2 have been found in lung tissue, with SVCT1 being identified solely in the blood vessels in one study [37], and on the apical surfaces of rat lung columnar epithelial cells in another study [52], both reporting widespread distribution of SVCT2.…”
Section: Introductionmentioning
confidence: 99%
“…The SVCTs show distinct tissue distribution, and together ensure the effective uptake and regulation of plasma and cellular ascorbate concentrations [36,35]. SVCT1 is responsible for uptake through the gut and re-absorption in the kidneys, and is thought to largely regulate plasma levels, whereas SVCT2 is concentrated in more metabolically active cells throughout the body, ensuring an adequate intracellular supply to support crucial intracellular functions [36,35].…”
Section: Introductionmentioning
confidence: 99%
“…VitC is thought to be actively transported by SVCT transporters in the placenta [50]; however, it also shares the same transporters as glucose via the GLUT-mediated transport of dehydroascorbic acid (DHA; the oxidized form of vitC) [51]. Thus, it may be speculated that the degree of glycemic control and, consequently, the level of oxidative stress and ascorbate oxidation rate may affect the bioavailability of vitC in T1DM pregnant women through competitive inhibition of DHA transport as proposed by Mann and Newton already in 1975 [52] and supported by the NHANES study 2003–2006 data [53]; here an inverse relationship between vitC and HbA1c was reported in 7697 non-diabetic participants.…”
Section: Discussionmentioning
confidence: 99%